The Impact of the Renin-Angiotensin-Aldosterone System on Inflammation, Coagulation, and Atherothrombotic Complications, and to Aggravated COVID-19 - Ekholm, M.; Kahan, T. (Frontiers in Pharmacology, 2021)
The most common cause of death in economically developed countries is atherosclerotic cardiovascular disease. Death rate caused by cardiovascular disease is expected to decrease in 2030, but will still retain its leading position due to an increasing prevalence in developing countries. A well-known cause of death within cardiovascular disease is coronary heart disease, and traditional risk factors for this disease are hypertension, hypercholesterolemia, diabetes mellitus, obesity, tobacco smoking, age, male sex and family history. Atherosclerosis is considered a disease caused by a chronic inflammation, associated with endothelial dysfunction, and several mediators of inflammation are up-regulated in subjects with atherosclerotic disease. Healthy, intact endothelium exhibits an antithrombotic, protective surface between the vascular lumen and vascular smooth muscle cells in the vessel wall. Oxidative stress is an imbalance between anti- and prooxidants, with a subsequent increase of reactive oxygen species, leading to tissue damage. The renin-angiotensin-aldosterone system is of vital importance in the pathobiology of vascular disease. Convincing data indicate that angiotensin II accelerates hypertension and augments the production of reactive oxygen species. This leads to the generation of a proinflammatory phenotype in human endothelial and vascular smooth muscle cells by the up-regulation of adhesion molecules, chemokines and cytokines. In addition, angiotensin II also seems to increase thrombin generation, possibly via a direct impact on tissue factor. However, the mechanism of cross-talk between inflammation and haemostasis can also contribute to prothrombotic states in inflammatory environments. Thus, blocking of the renin-angiotensin-aldosterone system might be an approach to reduce both inflammatory and thrombotic complications in highrisk patients. During COVID-19, the renin-angiotensin-aldosterone system is activated. The levels of angiotensin II contribute to the ongoing inflammation, which might result in a cytokine storm, a complication that significantly impairs prognosis. At the outbreak of COVID-19 concerns were raised about the use of angiotensin converting enzyme inhibitors and angiotensin receptor blocker drugs in patients with COVID-19 and hypertension or other cardiovascular comorbidities. However, the present evidence is in favour of continuing to use of these drugs. Based on experimental evidence, blocking the renin-angiotensin-aldosterone system might even exert a potentially protective influence in the setting of COVID-19.